Knowledge and Awareness of Polish Parents on Vaccination against Human Papillomavirus - Piotr Sypień; Tadeusz M. Zielonka (Vaccines, 2022)
Background: Human papillomavirus (HPV) vaccinations are rare among Polish children, and the reasons are scant. The objective was to evaluate the knowledge, attitude and awareness of parents about HPV vaccination to investigate reasons for low HPV vaccination coverage. Methods: 387 parents of children hospitalized at the Children’s Hospital were asked to participate in an anonymous and voluntary survey study. Three hundred and two surveys were returned. Results: Only 54% of participants have heard about HPV, while 26% know that it is a sexually transmitted disease. According to 71% of responders, vaccines are generally effective, and 63% claim that they are safe. However, only 5% of daughters and 4% of sons are vaccinated against HPV. A total of 25% of parents spoke with their doctor about HPV-related diseases and prevention methods. A higher level of education (p = 0.01), knowledge of sexually transmitted diseases (p < 0.0001), perceiving vaccination as an effective and safe prophylactic method (p < 0.0001), and conversations with a doctor (p < 0.0001) are strong motivators to vaccinate children against HPV. This decision is free of religious beliefs, origin, age, gender and the number of children. Conclusions: Polish parents have a positive attitude towards vaccination. They recognize the limitations of their knowledge and express a desire to further it. Educational activity is an important element of physicians’ work.